IMPLEMENTATION OF DIGITAL TECHNOLOGIES IN THE EDUCATIONAL ENVIRONMENT: MODERN APPROACHES TO LEARNING - J. Parlic-Bozovic; T. Vuletic (Многоязычие в образовательном пространстве)
The work is the result of an attempt to understand the patterns of placement of scientific content and the implementation of training in the framework of some subjects of the social and humanitarian profile, as well as the laws, organisation and evaluation of the educational process. Classical education with outdated forms of education has been condemned by some modern authors for the futility of teaching some subjects. Modern, interactive and multidimensional learning, which is a multidimensional need for a new generation of students, is at the same time a methodological challenge for individual subjects. The idea that the teacher is not the only carrier of knowledge is becoming increasingly relevant. New educational technologies open wide opportunities for self-education. Modern learning systems are designing an entirely new learning environment.